Perceptions and experiences of living with and providing care for multimorbidity: A qualitative interview study - Glenn Simpson; Leanne Morrison; Miriam Santer; Marisza Hijryana; Andrew Farmer; Hajira Dambha-Miller (Journal of Multimorbidity and Comorbidity)
Background Experiences of living with and seeking care for multimorbidity is a relatively under-researched field. By analysing experiences of people with multimorbidity, caregivers and care professionals, we can better understand the complex care needs of those with multimorbidity and identify improvements to care management. This paper reports findings from research that elicited the views of key stakeholders to inform future care practice and policy. Aim To elicit care recipient and care provider views to understand the care needs of those living with and seeking care for multimorbidity. Method A qualitative interview study using purposive sampling of those living with and providing care in multimorbidity. Results Increased support to those with multimorbidity and caregivers to navigate care systems was advocated. Establishing trusting care relationships featured prominently in participants accounts. Fragmented care, inadequate coordination and poor communication between care providers, were identified as system-wide challenges. There was agreement that integrated care models were needed, which delivered personalised care, such as shared decision-making, choice in care options and accessing services, and individualised care plans. Conclusion We found significant agreement among stakeholders on care need and management in multimorbidity. Understanding the experiences of those with multimorbidity, caregivers and care professionals, can inform future improvements in care management.